Iowa RBA, August 19, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for August 19, 1996. Highlights of the update include sightings of a Red Crossbill, Red-necked Phalaropes, Little Blue Herons, Snowy Egret, Piping Plover, and Least Tern. Also of note were the sightings of two exotic birds, a Ringed Turtle-Dove and a Ruddy Shelduck. Epson - sheet feed/flatbed